2020
DOI: 10.1002/cncy.22378
|View full text |Cite
|
Sign up to set email alerts
|

Acinar cell induced autolysis is a frequent occurrence in CytoLyt‐fixed pancreatic fine needle aspiration specimens: An analysis of 157 cytology samples

Abstract: Background Although 10% formalin is a standard preservative in pancreatic FNAs, the effect of CytoLyt on pancreatic tissue preservation has not been systematically explored. Methods Smears and cell blocks from CytoLyt‐fixed (CF‐CBs) and formalin‐fixed (FF‐CBs) pancreatic FNAs were blindly reviewed without knowledge of the fixative used, and the presence of tissue/tumor autolysis was noted. Controls included FF‐CBs from pancreatic FNAs, CF‐CBs from nonpancreatic FNAs, and 4 pancreatic FNAs with matched CF‐CBs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We recently showed that pancreatic EUS-FNA samples that were collected in CytoLyt frequently showed autolysis, as well as poor specimen preservation and suboptimal immunolabeling, and were thus more likely to be associated with indeterminate diagnoses (Figure 1). 24 Additionally, for pancreatobiliary samples, we found that smears, particularly when combined with cell blocks, were more likely to lead to a definitive, accurate diagnosis than ThinPrep samples alone. 15 This may be due to cytopathologists' familiarity and comfort level being greater with cytologic changes on smears than on liquid-based preparations, which have a tendency to cause cell shrinkage, and remove helpful features like necrotic debris and mucin.…”
Section: Technical Factorsmentioning
confidence: 74%
See 1 more Smart Citation
“…We recently showed that pancreatic EUS-FNA samples that were collected in CytoLyt frequently showed autolysis, as well as poor specimen preservation and suboptimal immunolabeling, and were thus more likely to be associated with indeterminate diagnoses (Figure 1). 24 Additionally, for pancreatobiliary samples, we found that smears, particularly when combined with cell blocks, were more likely to lead to a definitive, accurate diagnosis than ThinPrep samples alone. 15 This may be due to cytopathologists' familiarity and comfort level being greater with cytologic changes on smears than on liquid-based preparations, which have a tendency to cause cell shrinkage, and remove helpful features like necrotic debris and mucin.…”
Section: Technical Factorsmentioning
confidence: 74%
“…Issues related to specimen procurement, handling and preparation can significantly impact adequacy and diagnostic accuracy of pancreatic cytology specimens. 15,17,24,25 Factors such as specimen preparation artifacts, lesional cystic change, anatomically challenging locations, as well as gastroenterologists' skill in obtaining representative samples or performing multiple passes, all influence specimen quality and affect indeterminate rates. 11,26 In one study lesions with fewer passes were three times more likely to receive an atypical diagnosis.…”
Section: Technical Factorsmentioning
confidence: 99%
“…Tumor necrosis is caused by ischemia or apoptosis induced by high cellular proliferation. 1 Some authors have proposed including the necrotic background among the criteria for the diagnosis of pancreatic cancer on the cytology of FNA specimens. 2,3 Kiso et al 3 reported that the interobserver diagnostic agreement for a necrotic background in EUS-FNA specimens was moderate and that the necrotic background represented one of the important findings for differentiating malignant from benign lesions.…”
Section: Necrotic Backgroundmentioning
confidence: 99%
“…A necrotic background is one of the most common background features on the cytology of malignant tissues. Tumor necrosis is caused by ischemia or apoptosis induced by high cellular proliferation 1 . Some authors have proposed including the necrotic background among the criteria for the diagnosis of pancreatic cancer on the cytology of FNA specimens 2,3 .…”
Section: Necrotic Backgroundmentioning
confidence: 99%